SnoRNAs: The promising targets for anti-tumor therapy - Xiaoyun Hu; Wanlin Cui; Min Liu; Fangxiao Zhang; Yingqi Zhao; Mingrong Zhang; Yuhang Yin; Yalun Li; Ying Che; Xianglong Zhu; Yuxuan Fan; Xiaolan Deng; et al. (Elsevier, 2024)
Recently, small nucleolar RNAs (snoRNAs) have transcended the genomic "noise" to emerge as pivotal molecular markers due to their essential roles in tumor progression. Substantial evidence indicates a strong association between snoRNAs and critical clinical features such as tumor pathology and drug resistance. Historically, snoRNA research has concentrated on two classical mechanisms: 2'-O-ribose methylation and pseudouridylation. This review specifically summarizes the novel regulatory mechanisms and functional patterns of snoRNAs in tumors, encompassing transcriptional, post-transcriptional, and post-translational regulation. We further discuss the synergistic effect between snoRNA host genes (SNHGs) and snoRNAs in tumor progression. More importantly, snoRNAs extensively contribute to the development of tumor cell resistance as oncogenes or tumor suppressor genes. Accordingly, we provide a comprehensive review of the clinical diagnosis and treatment associated with snoRNAs and explore their significant potential as novel drug targets.